Oral Health Related Quality of Life Among the Staff of the Shahid Beheshti Dental School: Oral health quality in dental staff - Rivandi, Shiva; Mahshid Namdari; Mohammad Behnaz; Maryam Sadeghipour Rudsari; Maryam Ahmad Mehrabi (Journal of Dental School, 2023)
Objectives Health workers are considered as an important part of society and a role model for service recipients. Quality of life related to oral health is a common concept to assess the impact of oral conditions and the impact of dental interventions that affect people in many aspects such as physical, mental, social and ability to perform daily activities of life. The aim of this cross-sectional study was to assess the quality of life related to oral health among the staff of Shahid Beheshti Dental School. Methods This study was performed on 85 employees of Shahid Beheshti Dental School in 2021. The Participants completed the OHIP-49 (Oral health impact profile-49) questionnaire. Independent t-test, and one way ANOVA were used for data analyzing by SPSS 21 statistical software. Results The mean total score of OHIP was 13.86 with a standard deviation of 12.44. The most problematic subscale physical pain (20.65±14.01). The psychological disability and social disability subscales were significantly associated with female gender (p<0.05), and there was no relationship between the mean OHIP scores and the rest of measured demographic variables, including age, marital status, level of education, and chronic disease. Conclusion The results of the study showed that the quality of life related to oral health in dental staff was acceptable. On other hand, the Persian version of OHIP-49 questionnaire was validated to be used in Iran.